2009
DOI: 10.1111/j.1462-5822.2009.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylated proteins and distinct lipooligosaccharide glycoforms ofCampylobacter jejunitarget the human C-type lectin receptor MGL

Abstract: SummaryAn increasing number of bacterial pathogens produce an array of glycoproteins of unknown function. Here we report that Campylobacter jejuni proteins that are modified by the N-linked glycosylation machinery encoded by the pgl locus bind the human Macrophage Galactose-type lectin (MGL). MGL receptor binding was abrogated by EDTA and N-acetylgalactosamine (GalNAc) and was successfully transferred to Escherichia coli by introducing the C. jejuni pgl locus together with a glycan acceptor protein. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 53 publications
(133 reference statements)
3
78
0
1
Order By: Relevance
“…Although no clear differences in reactivity to patient sera were observed, this does not preclude a role for the pEtN-glycan in innate immunity or in modifying host cell interactions. For example, previous studies have shown that C. jejuni N-linked glycoproteins and LOS displaying terminal GalNAc can bind the human macrophage galactose-type lectin (MGL) (64). Although speculative, the addition of pEtN to the N-glycan may block interactions between the previously terminal GalNAc of the canonical glycan and MGL, thus disrupting adherence between C. jejuni and MGL-expressing dendritic and macrophage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although no clear differences in reactivity to patient sera were observed, this does not preclude a role for the pEtN-glycan in innate immunity or in modifying host cell interactions. For example, previous studies have shown that C. jejuni N-linked glycoproteins and LOS displaying terminal GalNAc can bind the human macrophage galactose-type lectin (MGL) (64). Although speculative, the addition of pEtN to the N-glycan may block interactions between the previously terminal GalNAc of the canonical glycan and MGL, thus disrupting adherence between C. jejuni and MGL-expressing dendritic and macrophage cells.…”
Section: Discussionmentioning
confidence: 99%
“…hMGL is equipped with a partial dileucine zipper and with YENF internalization motifs [11]. This receptor is involved in the recognition of a large plethora of pathogens by DCs [12][13][14][15] and in the maintenance of T-cell homeostasis [16]. Moreover, in vivo, MGL appears to play a crucial role in close proximity of the endothelial structures of lymph nodes and thymus, where iDCs are hampered in their migration activity until maturation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of N-linked glycosylation machinery leads to decreased colonisation ability of bacteria, as well as to a reduction of adherence to and invasion of human epithelial cells suggesting that some of these glycoproteins may play a role of adhesins [57][58][59][60]. Although it remains unknown whether Campylobacter N-glycosylation is required for adhesion there is some evidence that it might influence host immune response [61,62].…”
Section: Campylobacter Adhesion Involving Lectin-glycan Interactionmentioning
confidence: 99%
“…Excessive production of IL-10 also inhibited maturation of dendritic cells, thus, further assisting bacteria to evade host immune response [64]. In the study by van Sorge et al [61] it was shown that N-linked glycoproteins of C. jejuni interact with Ctype lectins of macrophage galactose-type lectins (MGL). These findings suggest a possible role of Campylobacter N-lined glycosylation system for modulation of host immune responses.…”
Section: Campylobacter Adhesion Involving Lectin-glycan Interactionmentioning
confidence: 99%
See 1 more Smart Citation